2022
DOI: 10.21203/rs.3.rs-1454838/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilisation of services along the continuum of maternal healthcare during the COVID-19 pandemic in Lubumbashi, DRC: findings from a cross-sectional household survey of women

Abstract: Introduction:The continuum of maternal care along antenatal (ANC), intrapartum, and postnatal care (PNC) is fundamental for protecting women’s and newborns’ health. The COVID-19 pandemic and accompanying mitigation measures interrupted the provision and use of these essential services globally. This study examines maternal healthcare utilisation along the continuum during the COVID-19 pandemic in the Democratic Republic of the Congo, and explores factors associated with use of the full continuum.Methods:This i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“… Galle A., Kavira G., Semaan A., et al, 2022. DR. Congo [ 30 ]. MHC utilisation along the continuum during the COVID-19 pandemic in the Democratic Republic of the Congo, and factors associated with use of the full continuum Cross-sectional survey March 2020–May 2021 604 women (15–49 years) who were pregnant Of the women who gave birth during the COVID-19 pandemic, 61% had ANC 4+ consultations, most had a skilled birth attendant (97%), and more than half (55%) had a PNC check for themselves and the newborn.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Galle A., Kavira G., Semaan A., et al, 2022. DR. Congo [ 30 ]. MHC utilisation along the continuum during the COVID-19 pandemic in the Democratic Republic of the Congo, and factors associated with use of the full continuum Cross-sectional survey March 2020–May 2021 604 women (15–49 years) who were pregnant Of the women who gave birth during the COVID-19 pandemic, 61% had ANC 4+ consultations, most had a skilled birth attendant (97%), and more than half (55%) had a PNC check for themselves and the newborn.…”
Section: Resultsmentioning
confidence: 99%
“…This was similar in Ethiopia where economic suffering prevented women from being able to pay for transportation [ 8 ]. A cross-sectional study of 1600 pregnant women in Democratic republic of Congo between March 2020–May 2021 identified similar issues [ 30 ]. This study showed that lack of money along with vaccine hesitancy were some of the reason’s women did not access MHC services [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…Sufficient supply, maintaining core interventions, expanding the nonphysician workforce, and deploying telehealth are some adaptation measures to optimize care (Syawaludin & Fikri, 2019). In the COVID-19 pandemic, the government must reinvest in maternal and child health by building more resilient maternal health services supported by political commitment, multisectoral engagement, and assistance from international partners (Galle et al, 2022). Therefore, there is a need for multisectoral investments that provide highquality care that ensures continuity and is available to all segments of the population.…”
Section: Introductionmentioning
confidence: 99%